The Effectiveness of Counseling on Exclusive Breastfeeding Practices for Mothers in Makassar City: A Quasi-Experimental Study - Azrida Machmud; Yusrah Taqiyah (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Breastfeeding is essential for infant health and development, yet its success is influenced by maternal knowledge and counseling support. This study aimed to analyze differences in breastfeeding among mothers who received counseling and those who did not before and after delivery. A quasi-experimental study with a two-group pre-posttest control group design was conducted at Masyita Maternity Hospital and Kassi-Kassi Primary Health Care Center, Makassar City, from September to December 2023. The population was pregnant women present during the study period, with a total sample of 56 respondents selected using purposive sampling, consisting of 28 in the intervention group and 28 in the control group. Data were analyzed using the Wilcoxon Signed Ranks Test and Mann-Whitney Test. The results showed a significant difference in maternal knowledge between the intervention and control groups (p=0.038). However, no significant differences were found in breastfeeding outcomes at the first month (p=0.164) and the second month postpartum (p=0.279). These findings indicate that although counseling improved maternal knowledge, breastfeeding success was achieved in both groups due to their generally good knowledge. Intensive counseling during the third trimester, continued with postnatal support through home visits and information provision up to six months postpartum, is essential to optimize exclusive breastfeeding achievement.